Exploring the Challenges Faced by the Bachelor’s level Students in Reading English Textbooks - Tiwari, Hari Prasad (Journal of NELTA Gandaki, 2022)
Reading textbooks written in second or foreign language is considered more challenging than written in reader’s mother tongue. If the textbooks are written considering the level of the students, they read and comprehend the texts without extra effort. With this in mind, the study tries to explore the challenges faced by the bachelor level second year students while reading the textbook ‘Readings for the New Horizons’. The participants of this descriptive phenomenological study consisted of 15 students studying specialization English in Bachelor of Education (B.Ed.) second year. I employed purposive sampling to select the participants and unstructured interview to collect the data. The collected data was transcribed and thematized and findings of the study were presented and analyzed employing descriptive techniques of qualitative data analysis. The findings revealed that students consider unfamiliar words as the major challenge followed by length of the reading texts, less proficient in English, sentence structure, content included in the textbook, number of lessons or reading texts incorporated in the textbook and lack of reading habits. The teachers need to involve students in intensive reading to overcome the challenges and to develop the habit of reading texts written in second language.